The Effectiveness of Educational Management in Enhancing the Learning Process at Madrasah Diniyah Sore PP. Miftahul Ulum Putri - Mufarrohah, Lailatul; Husni, Muhammad (Universitas PGRI Sumatera Barat, 2025)
This study aims to examine the implementation of educational management at Madrasah Diniyah Sore PP. Miftahul Ulum Putri, a non-formal Islamic educational institution that complements evening diniyah learning. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results indicate that educational management at the madrasa has been effectively implemented across four key dimensions: planning, organizing, implementation, and evaluation. Planning is conducted contextually, albeit without formal documentation. The organizational structure is well-established with systematic class levels, while instructional delivery focuses on the afternoon session as an introductory overview for evening diniyah lessons. Evaluation is performed informally through direct observations of student engagement and comprehension. The presence of the afternoon diniyah program has demonstrably enhanced the academic preparedness and spiritual growth of female students in a sustainable manner. However, challenges remain in integrating technology and establishing measurable evaluation systems. Therefore, strengthening management through documentation and pedagogical innovation is both essential and urgent to enhance the madrasa’s effectiveness and relevance in the modern era.